Численное определение контактных усилий при горячей раскатке заготовки подшипникового кольца - Автономова, Людмила Владимировна; Грозенок, Евгений Денисович; Степук, Александр Владимирович; Погорелов, Сергей Юрьевич (НТУ "ХПИ", 2017)
Методом конечного элемента проведено численное моделирование процесса горячей раскатки заготовки подшипникового кольца. Для определения параметров напряженно-деформированного состояния была решена нестационарная контактная краевая термовязкопластическая задача при неравномерном и постоянном распределении начального поля температур в заготовке. Наблюдается увеличение усилия раскатки неравномерно нагретой заготовки, полученной при штамповке способом однопроходной и двухпроходной формовки. Незначительное повышение энергозатрат на технологическую операцию раскатки позволяет получить подшипниковые кольца с улучшенными прочностными характеристиками.

The simulation design of hot rolling process out bearing ring is conducted applying the method of finite elements. A mathematical model to process the high-speed deformation of the ring cylindrical workpiece is presented. To determine parameters of the bearing ring stress-deformed state, during the deforming, the non-stationary contact viscous plastic boundary value problem under non-uniform and instant temperature fields distribution in the workpiece was numeral solved applying the method of finite element based on incremental Lagrange-Euler independent approach. Values of contact forces (pressures) between a roller and a workpiece were defined. The reviewed analysis of overall contact forces variation demonstrated the rolling-out forces increase for initially non-uniformly heated workpiece. The contact forces values are also defined in the hot rolling ring out for rational distribution of fibred structure within the workpiece material after the two-step molding with the more irregular heating of the workpiece. The small growth in energy consumption happening because of the increasing forces during the rolling-out operations leads to producing the bearing rings material having the rational distribution of fibred structures. Such distribution allows to achieve the higher durability of the bearing rings, and results in their robustness increase during the whole working cycle.
The contact forces numerical valuation during hot rolling of the bearing ring
Keywords: кольцо подшипника; моделирование; термовязкопластичность; метод конечных элементов; bearing ring; hot ring rolling; modeling; thermal visco-plasticity; finite element method